Engraving after Labille-Guiard - Élisabeth of France - After Adélaïde... (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons pour la demo du fonds documentaire. Titre: Engraving after Labille-Guiard - Élisabeth of France.
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; tableau